Early Serum Infliximab Levels in Pediatric Ulcerative Colitis - deBruyn, Jennifer C. C.; Jacobson, Kevan; El-Matary, Wael; Wine, Eytan; Carroll, Matthew W.; Goedhart, Caitlin; Panaccione, Remo; Wrobel, Iwona T.; Huynh, Hien Q. (Frontiers in Pediatrics, 2021)
Background: Data on serum infliximab concentrations during induction in pediatric ulcerative colitis are limited. The study aim is to evaluate the relationship between serum infliximab concentrations during induction and short-term clinical remission in children with ulcerative colitis. Methods: We carried out a prospective, multi-center cohort study in pediatric patients with ulcerative colitis. Serum infliximab concentrations were collected at peak dose #1, week 1, trough pre-dose #2, and trough pre-dose #3. Infliximab dosing was left to investigator discretion. Clinical remission was defined by pediatric ulcerative colitis activity index <10 at week 8. Results: Twenty-four of thirty-four subjects (71%) achieved clinical remission at week 8. The median infliximab concentrations were 33.0 μg/mL (interquartile range: 26.5–52.1 μg/mL) pre-dose #2 and 22.5 μg/mL (interquartile range:15.9–32.3 μg/mL) pre-dose #3. Trough pre-dose #2 infliximab concentration yielded area under receiver operator characteristic curve 0.7, 95% CI: 0.5–0.9 in predicting week 8 clinical remission; a cut-off of 33.0 μg/mL yielded 62.5% sensitivity, 66.7% specificity. Trough pre-dose #3 infliximab concentrations were lower for subjects <10 years compared to ≥ 10 years [median 15.9 μg/mL, interquartile range (IQR) 8.5–21.8 μg/mL vs. 27.7 μg/mL, IQR 17.2–46.7 μg/mL, p = 0.01] and correlated with baseline weight (Spearman's rank correlation coefficient 0.45, p = 0.01). The median half-life following first IFX dose was 6.04 days (IQR 5.3–7.9 days). Conclusions: Infliximab concentrations ≥33 μg/mL prior to the second dose were associated with week 8 clinical remission. As young age and low body weight impact infliximab concentration, prospective studies with proactive adjustment in pediatric patients with ulcerative colitis should be carried out. Clinicians caring for children with UC should diligently adjust and monitor infliximab to optimize response.